Corporate business hubs as a form of MNC’s open innovation endeavours : the case of Henkel DX - Wank, Philipp Marcel (2021)
This dissertation aimed to find out why multinational corporations set up corporate business hubs along with the identification and examination of factors influencing the relationship of a corporate business hub to its parent company with regards to the hub’s innovation success. Considering this, a leading multinational corporation, Henkel, with its corporate business hub Henkel DX innovation hub, was selected and in the form of a single case study investigated. Therefore, existing literature was considered and primary research in the form of semistructured interviews was conducted with employees from the parent company as well as from the hub’s management team. The empirical findings show, that the main reasons fo multinational corporations to set up corporate business hubs are the generation of synergies and cost savings, the assurance of a clear allocation and responsibility regarding a corporation’s innovation leaders, the addition of a new marketing and communication dimension as well as the addition of another open innovation unit driving overarching innovation endeavours. The main influence factors on the relationship between hub and parent company leading to innovation success from hub perspective are budget, budget management, strategy, perception, and responsibility of the hub, employees, diversity, and communication. From the parente company perspective the main influence factors on the relationship to the hub leading to innovation success are also strategy, budget, communication, and responsibility, but also the quality level of the hub’s activities and corresponding KPI’s.